The Effectiveness of Active Management of the Third Stage of Labor Regarding Early Postpartum Hemorrhage - Mongkolprathumrut, Sureerut (Journal of Health Science of Thailand, 2017)
The retrospective study of effectiveness about active management of the third stage of labor (AMTSL) regarding early postpartum hemorrhage, Sena Hospital, Phra Nakhon Si Ayutthaya province. Parturients with vaginal delivery were divided into two groups in the conventional phase (October 1999 to September 2005) and the active management in the AMTSL phase (March 2007 to February 2008). Comparisons on delivery were made between the two groups and presented in percentage and differences were established by Fisher’s exact test. The study showed that the active management of the third stage of labor had more advantages than the conventional treatment significantly at p < 0.05. The severity of blood volume loss was at the level 1 (500-799 millilitre) and level 2 (800-1,499) with minimal sign and sympthom of postpartum hemorrhage. Blood transfusion rate significantly decreased from 34.58 percent to 10 percent, while in AMTSL phase no hysterectomy was required or no one died from postpartum hemorrhage. In conclusion, active management of the third stage of labor strategy should be engaged in basic management of the third stage of labor, for more healthy and safety of parturients.